2022
DOI: 10.1108/ijtc-05-2022-0131
|View full text |Cite
|
Sign up to set email alerts
|

Are consumers influenced by the use of green practices in five-star hotels: an assessment of guest's revisit intentions, inclusive ratings and hotel performance

Abstract: Purpose This study aims to find out the influence of green practices used by the five-star hotels on the guest’s online hotel assessment and their revisit intentions. It also evaluated how the use of green practices by the hotels influenced the guest’s willingness to pay a premium price. Apart from the conventional hotel service attributes, this study also identified some new and innovative services offered by the hotels which have an overall effect on the guest’s revisit intentions. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Guests are becoming more concerned about the environment due to the rapid growth of health and environmental concerns which in turn, influence their purchasing behaviour (Han et al, 2011). Consumers constantly search for eco-friendly products to show their devotion to constructing a greener community (Grosbois and Fennell, 2022;Gupta et al, 2023). It has been demonstrated that implementing eco-friendly or sustainable strategies which have a long-lasting impact on customer loyalty can enhance an organisation's brand reputation and competitive edge (Gupta et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Guests are becoming more concerned about the environment due to the rapid growth of health and environmental concerns which in turn, influence their purchasing behaviour (Han et al, 2011). Consumers constantly search for eco-friendly products to show their devotion to constructing a greener community (Grosbois and Fennell, 2022;Gupta et al, 2023). It has been demonstrated that implementing eco-friendly or sustainable strategies which have a long-lasting impact on customer loyalty can enhance an organisation's brand reputation and competitive edge (Gupta et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers constantly search for eco-friendly products to show their devotion to constructing a greener community (Grosbois and Fennell, 2022;Gupta et al, 2023). It has been demonstrated that implementing eco-friendly or sustainable strategies which have a long-lasting impact on customer loyalty can enhance an organisation's brand reputation and competitive edge (Gupta et al, 2023). To differentiate their brand and recognition from many other competitors in the industry, many hotels in Fiji islands are now employing green or environmentally friendly administration procedures and incorporating ecological strategies and techniques as directed by the local government (World Travel and Tourism Council, Fiji, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations